2001
DOI: 10.1210/jcem.86.1.7117
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Angiotensin-Converting Enzyme Gene Polymorphism and Insulin Resistance in Never-Treated Hypertensive Patients

Abstract: The association between angiotensin-converting enzyme (ACE) gene polymorphism and insulin resistance (IR) in hypertensive subjects remains controversial. Thus, we evaluated the possible association between IR and ACE gene polymorphism in a group of hypertensive, never-treated patients compared with that in a normotensive control group. We enrolled 200 (114 men and 86 women; age, 45.5 +/- 4.7 yr) hypertensive patients and 96 (54 men and 42 women; age, 44.0 +/- 4.7 yr) normotensive subjects. A double PCR assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…However, no association between I/D genotypes of ACE and plasma PAI-1 concentration was found by others [21,22]. The association between ACE gene polymorphism and insulin resistance (IR) in hypertensive subjects remains also controversial [23][24][25][26]. Perticone et al [24] referred that patients with the DD genotype never treated for hypertension had a higher fasting concentration of insulin and IR HOMA than the hypertensive patients with I allele of the ACE gene polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…However, no association between I/D genotypes of ACE and plasma PAI-1 concentration was found by others [21,22]. The association between ACE gene polymorphism and insulin resistance (IR) in hypertensive subjects remains also controversial [23][24][25][26]. Perticone et al [24] referred that patients with the DD genotype never treated for hypertension had a higher fasting concentration of insulin and IR HOMA than the hypertensive patients with I allele of the ACE gene polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is closely linked to the metabolic syndrome (7), and the renin-angiotensin system (RAS) plays a central role in the regulation of insulin sensitivity (8)(9)(10), as well as in the regulation of blood pressure and sodium homeostasis (11). Many studies have examined the genetic involvement of homozygous deletion polymorphism (DD) in exon 16 of the angiotensin-converting enzyme gene (ACE) in insulin resistance, but their results have been controversial (12)(13)(14). The association between ACE insertion-deletion (I/D) polymorphism in intron 16 and cardiovascular phenotypes has also been studied, with the main result being that the D allele is a genetic risk for coronary artery disease or left ventricular hypertrophy (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies found a significant association between the ACE I/D polymorphism and type 2 diabetes [12, 14, 25, 26], others did not [13]. Similarly, some studies found that individuals with the DD genotype had an increased insulin resistance [27], whereas others reported an increased insulin sensitivity in subjects with the DD genotype [28, 29]. Whilst several studies reporting a significant association were conducted in Asian populations [12, 25, 26], raising the possibility of differences across ethnicities, all of these studies were small.…”
Section: Discussionmentioning
confidence: 99%